Examining Peer Communication and it’s influence on HIV/AIDS Awareness, Attitudes, and Behaviours among Youth in Malaysia - Yusha Irdina Shareeman; Najmi Nafis Khairul Azli; Mohamad Hafifi Jamri; Abdul Rauf Ridzuan; Mohd Khairie Ahmad; Nurzali Ismail (Jurnal Communio : Jurnal Jurusan Ilmu Komunikasi, 2026)
This study examines the influence of peer groups on HIV/AIDS awareness, attitudes, and behaviors among youth. Adolescents aged 10 to 24 are highly vulnerable to peer influence, which can shape both positive and risky behaviors related to HIV/AIDS. Despite ongoing awareness campaigns, many young people continue to engage in unsafe practices such as unprotected sex and substance abuse, increasing their risk of HIV infection. Therefore, this study aims to assess the level of HIV/AIDS awareness among youth, examine the influence of peer groups on attitudes and behaviors, and evaluate the effectiveness of positive peer influence in HIV/AIDS prevention. A quantitative research design was used, involving 108 respondents from various educational and community settings in Malaysia. Data were collected through structured questionnaires distributed online and offline and analyzed using SPSS version 27. The findings revealed that respondents generally had a high level of HIV/AIDS awareness, particularly regarding transmission through unprotected sex and needle sharing. Peer influence was also found to significantly affect attitudes and behaviors, with many respondents reporting that peers encouraged positive health practices such as condom use and health awareness. The study concludes that peer-led and youth-centered strategies are essential for strengthening HIV/AIDS prevention efforts among youth.